1997
DOI: 10.1021/bi9627323
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Pressure Profile in Membranes:  A Physical Mechanism of General Anesthesia

Abstract: A mechanism of general anesthesia is suggested and investigated using lattice statistical thermodynamics. Bilayer membranes are characterized by large lateral stresses that vary with depth within the membrane. Incorporation of amphiphilic and other interfacially active solutes into the bilayer is predicted to increase the lateral pressure selectively near the aqueous interfaces, compensated by decreased lateral pressure toward the center of the bilayer. General anesthesia likely involves inhibition of the open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
278
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(290 citation statements)
references
References 20 publications
10
278
2
Order By: Relevance
“…This implies the absence of nonspecific perturbations of lipid membranes by minocycline. However, it can not be excluded that minocycline acts at the protein-lipid interface causing redistribution of membrane lateral pressure sensed by specific membrane proteins [57].…”
Section: Discussionmentioning
confidence: 99%
“…This implies the absence of nonspecific perturbations of lipid membranes by minocycline. However, it can not be excluded that minocycline acts at the protein-lipid interface causing redistribution of membrane lateral pressure sensed by specific membrane proteins [57].…”
Section: Discussionmentioning
confidence: 99%
“…Such conductance increases could occur by the membrane acting on Na þ channels to stabilize the open state, or by the lipid membrane directly becoming leaky to Na þ ions. In support of the indirect pathway, it has been proposed (21), and supported by statistical thermodynamics (3,22) and coarse-grain modeling (23), that alcohol changes the lateral pressure within the membrane and that this increase can bias ion channels toward the closed state. In support of the direct pathway it has be shown that both ethanol (24) and other anesthetics (25) can change the permeability of lipid membranes.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, interest has focused on distortions of the lipid bilayer caused by the presence of a membrane protein and on how these distortions could depend on elastic properties of the bulk lipid bilayer such as its spontaneous curvature (3)(4)(5)(6)(7). The spontaneous curvature of a lipid, C 0 , is the reciprocal of the spontaneous radius of curvature, R 0 , and is the curvature that one monolayer of a bilayer would adopt if it was allowed to bend freely, without the constraint imposed from being packed back to back with another monolayer in a bilayer (8).…”
mentioning
confidence: 99%